Psychometric properties of the Chinese version of the spiritual care competency scale in nursing practice: a methodological study - Fan Li; Yanli Hu; René Van Leeuwen (BMJ Open)
Objectives To determine the validity and reliability of the Spiritual Care Competency Scale (SCCS) among nurses in China.Design Methodological research.Methods After the SCCS was translated into Chinese, the validity and reliability of the Chinese version of the SCCS (C-SCCS) were evaluated using a convenience sample of 800 nurses recruited from different healthcare centres. The construct validity of the C-SCCS was determined by an exploratory factor analysis (EFA) with promax rotation. Pearson’s correlation coefficients of the C-SCCS and the Palliative Care Spiritual Care Competency Scale (PCSCCS-M) were computed to assess the concurrent validity and construct validity of the C-SCCS. To verify the quality of the component structure, we conducted a confirmatory factor analysis (CFA). We tested the internal consistency and stability of the measure using Cronbach’s alpha coefficient and the Guttman split-half coefficient, respectively, and a factorial analysis was performed.Results A total of 709 participants completed the questionnaire (response rate: 88.63%), and all completed questionnaires were suitable for analysis. Three factors were abstracted from the EFA and explained 58.19% of the total variance. The Cronbach’s alpha coefficients of the three subscales were .93, .92, and .89, and the Guttman split-half coefficient for the C-SCCS was .84. The CFA indicated a well-fitting model, and the significant correlations between the C-SCCS and the PCSCCS-M (r=0.67, p<0.01) showed adequate concurrent validity. Nurses’ education and income level showed a significant association with the C-SCCS score.Conclusion The C-SCCS was shown to be a psychometrically sound instrument for evaluating Chinese nurses’ spiritual care competencies.